Multimodal LA-ICP-MS and nanoSIMS imaging enables copper mapping within photoreceptor megamitochondria in a zebrafish model of Menkes disease. Issue 3 (6th March 2018) - Ackerman, Cheri M.; Weber, Peter K.; Xiao, Tong; Thai, Bao; Kuo, Tiffani J.; Zhang, Emily; Pett-Ridge, Jennifer; Chang, Christopher J.
Abstract : Coregistering quantitative high-resolution metal imaging with fluorescence imaging identifies copper accumulation in megamitochondria within intact neuroretinal slices. Abstract : Copper is essential for eukaryotic life, and animals must acquire this nutrient through the diet and distribute it to cells and organelles for proper function of biological targets. Indeed, mutations in the central copper exporter ATP7A contribute to a spectrum of diseases, including Menkes disease, with symptoms ranging from neurodegeneration to lax connective tissue. As such, a better understanding of the fundamental impacts of ATP7A mutations on in vivo copper distributions is of relevance to those affected by these diseases. Here we combine metal imaging and optical imaging techniques at a variety of spatial resolutions to identify tissues and structures with altered copper levels in the Calamity gw71 zebrafish model of Menkes disease. Rapid profiling of tissue slices with LA-ICP-MS identified reduced copper levels in the brain, neuroretina, and liver of Menkes fish compared to control specimens. High resolution nanoSIMS imaging of the neuroretina, combined with electron and confocal microscopies, identified the megamitochondria of photoreceptors as loci of copper accumulation in wildtype fish, with lower levels of megamitochondrial copper observed in Calamity gw71 zebrafish. Interestingly, this localized copper decrease does not result in impaired photoreceptor development or altered megamitochondrial morphology, suggesting the prioritization of copper at sufficient levels for maintaining essential mitochondrial functions. Together, these data establish the Calamity gw71 zebrafish as an optically transparent in vivo model for the study of neural copper misregulation, illuminate a role for the ATP7A copper exporter in trafficking copper to the neuroretina, and highlight the utility of combining multiple imaging techniques for studying metals in whole organism settings with spatial resolution.